2009
DOI: 10.1097/bot.0b013e3181ba46d3
|View full text |Cite
|
Sign up to set email alerts
|

Distal Radius Fractures

Abstract: Distal radius fractures are a common injury, particularly in the elderly population. Severity of these fractures is directly related to the bone mineral density of the patient, and clinical results are dependent on this parameter as well. In terms of treatment, several options exist. Nonoperative management consists of closed treatment with casting. Operative treatment options include intrafocal pinning, nonbridging and bridging external fixation, arthroscopic-assisted external fixation, and various methods of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 82 publications
1
45
0
9
Order By: Relevance
“…Bu kırıkların yıllar içinde daha iyi anlaşılması, el bileği biyomekaniğinin irdelenmesi ve günümüzdeki teknolojik gelişmeler, tedavinin evrimleşmesine neden olmuştur. [5][6][7] Son yıllarda gelişen ve çok iyi sonuçlar alınan cerrahi tedavi seçenekleri olmasına rağmen, bazı kırıklar için kapalı redüksiyon ve alçı ile tespit seçeneği halen geçerlidir. Konservatif tedavi, kendine göre zorlukları olan zahmetli bir yöntemdir.…”
Section: Tedavi Planı Ve Uygulamaunclassified
See 2 more Smart Citations
“…Bu kırıkların yıllar içinde daha iyi anlaşılması, el bileği biyomekaniğinin irdelenmesi ve günümüzdeki teknolojik gelişmeler, tedavinin evrimleşmesine neden olmuştur. [5][6][7] Son yıllarda gelişen ve çok iyi sonuçlar alınan cerrahi tedavi seçenekleri olmasına rağmen, bazı kırıklar için kapalı redüksiyon ve alçı ile tespit seçeneği halen geçerlidir. Konservatif tedavi, kendine göre zorlukları olan zahmetli bir yöntemdir.…”
Section: Tedavi Planı Ve Uygulamaunclassified
“…Başlangıç grafisinde parçalanma ve aşırı açılanma gösteren veya eklem içine uzanan kırık-lar, ulnada eşlik eden kırıklar veya ileri derece osteoporozu olan kırıklar, stabil olmayan kırıklardır ve bu, alçı içinde ikincil kayma ihtimali yüksek kırıklar anlamına gelir (Şekil 4, 5). [5][6][7][8][9] Konservatif tedavinin endikasyonları; 1) kaymamış eklem dışı ve eklem içi kırıklar, 2) kaymış ama kapalı redüksiyondan sonra stabil olan kırıklar ve 3) yaşlıların stabil olmayan kırıklarıdır. [5,9] Kaymamış veya çok az kaymış (5º'den az dorsal açı-lanma veya 2 mm'den az kısalma gösteren) kırıklar alçı ile tedavi edilebilirler (Şekil 4).…”
Section: Tedavi Planı Ve Uygulamaunclassified
See 1 more Smart Citation
“…Although cast immobilization was almost the only universal treatment in past, today it is progressing to operative interventions. Although most injured people are elderly, recent researches revealed that there is an increasing 4,5 incidence rate of this fracture in all age range. Osteoporosis is the prime risk factor for fracture in elderly patients whereas motor vehicle accident is the leading cause in young adult and 6,7 adult population.…”
Section: Introductionmentioning
confidence: 99%
“…8 The current trend in surgical stabilization is the use of a volar plate to internally fix unstable or displaced distal radius fracture patterns. 19,25 Proponents of this method cite biomechanical benefits, procedural advantages, and potentially lower complication rates compared with dorsal plating options. 34 Despite the benefits offered with volar plating, a seemingly rare consequence of using this technique is irritation and subsequent rupture of the flexor pollicis longus (FPL) and flexor digitorum profundus (FDP) tendon to the index finger.…”
Section: Introductionmentioning
confidence: 99%